ANALISIS YURIDIS KEDUDUKAN HUKUM ADAT DAN PERANAN NOTARIS-PPAT DALAM PROSES PENDAFTARAN TANAH MENURUT UNDANG-UNDANG POKOK AGRARIA DI KOTA SORONG PAPUA BARAT - Dwi Pratiwi Markus; Amin Purnawan (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2017)
This research aims (1) To know and analyze how the process of registration of customary land (2) To know and analyze the position of customary law and the role of Notary-PPAT in the process of land registration in Sorong City West Papua reviewed: According to the Principal Agrarian Law. This research uses a juridical-empirical approach. Yudiris is used to analyze rules relating to customary law and land, while empirical is used to analyze laws based on the behavior of people who always interact in daily life. The result of this research are (1) Government of Indonesia recognition of the existence of land and customary law is set forth in UUPA and PP. 24 of 1997 on Land Registration, so that in the process of registration of customary land in Sorong city is not much different from the registration of land in general. Only the registration of customary land in Sorong must be proven by several conditions that specify in local customary law and has been arranged also in the PP. No. 24 of 1997 (2) UUPA itself is a national agrarian law whose presence is based on indigenous laws of Indonesia known as customary law, so to conduct registration of land in Sorong City must use letters of customary release from the local customary chief, in this process the role of Notary-PPAT is needed in making the declaration of customary release and the role of PPAT in helping people who do not understand the rules of local custom in the process of registration of customary land as long as it does not violate the rules related to PPAT authority set by PerKaBPN No. 8 Year 2013.Keywords: Land, Customary Law, Notary-PPAT